Potential Of Ozone Treatment As A pollution Control Method For Gaseous Effluents From Internal Combustion Engines. - Fernando, W.J.N.
Internal combustion engines are widely used as mobile units in the transport sector and commercially used as stationary units in the power production and agricultural sectors. Emissions from internal combustion engines usually consist of oxides of nitrogen, carbon dioxide, carbon monoxide, sulphnr dioxide, and un-combusted hydrocarbons in addition to unconverted oxygen and nitrogen.